The Need for Stability in Paid Dementia Care: Family Caregiver Perspectives. (April 2023) - Reckrey, Jennifer M.; Perez, Sasha; Watman, Deborah; Ornstein, Katherine A.; Russell, David; Franzosa, Emily
Paid caregivers (e.g., home health aides, home care workers) provide essential care to people with dementia living at home; this study explored family caregiver perspectives on the role and impact of paid caregivers in home-based dementia care. We conducted semi-structured interviews with family caregivers ( n = 15) of people with advanced dementia who received long-term paid care at home in New York between October 2020 and December 2020. We found that given the vulnerability resulting from advanced dementia, family caregivers prioritized finding the "right" paid caregivers and valued continuity in the individual providing care. The stable paid care that resulted improved outcomes for both the person with advanced dementia (e.g., eating better) and their family (e.g., ability to work). Those advocating for high quality, person-centered dementia care should partner with policymakers and home care agencies to promote the stability of well-matched paid caregivers for people with advanced dementia living at home.